An introduction to Western philosophy : ideas and argument from Plato to Popper - Flew, Antony, 1923-2010. (New York, N.Y. : Thames and Hudson, 1989)
Aristotle and Aquinas - Pascal - Descartes and the Cartesian revolution - Hume - The logical and the psychological - Plato and Locke; Kant - Leibniz - The soul.
Starting with Plato -- Theory of Forms -- Plato's own criticism of that theory -- Plato and the longing for objective values -- What objectivism and subjectivism, in our broad senses, do and do not involve -- Subjectivism of Hume -- Humean critique applied to four kinds of objectivism -- Subjectivism, in a narrower sense, refuted -- Ultimate ends and intrinsic values -- Making room for moral argument -- Presuppostions of pre-existence and immortality -- From the Forms to immortality -- Soul and the person -- Aristotle and a materialist view of man -- Aristotle and Aquinas -- Impossibility and contradiction -- Faith and reason -- Stratonician presumption -- Ontological argument -- First Mover -- Cosmological arguments -- Arguments to design -- Appeal to personal experience -- Pascal's wager -- Elementary ideas -- Aristotelian conservatism: splitting hairs not starting hares -- Radical onslaughts: predestination -- Radical onslaughts: hard determinism -- Necessity, avoidability, and foreknowledge -- Laws and inevitability -- Choice and desire -- Method for a new beginning -- Protestant individualism secularized -- Cartesian foundations for knowledge -- Rationalist vision -- Ghost in the machine -- Hume opposes Descartes -- Two conditions of authentic doubt -- Inexpressible doubt and logically private language -- Possible error and actual knowledge -- Certainty and conception, clear and distinct -- Representative and causal theories -- Idealist vision of George Berkeley -- Agnosticism of Hume and Kant -- Argument from illusion -- Seeing things and having experiences -- Philosophical analyses and scientific accounts -- Mathematics and the rationalist hope -- Hume's fork -- Arguments from experience -- Proposed epistemological foundations for mathematics -- Nature of the apriori -- Logical and the psychological -- Mathematics, pure and applied -- Confronting Plato with Locke -- General words and Locke's abstract general images -- Two tests for souls and two concepts of soul -- Classifications as a human activity -- Essence and existence (i) existentialism -- Essence and existence (ii) essentialism -- 'Scientific socialism' and social science -- Linguistic philosophy and philosophy.
Includes bibliographical references (pages 491-498).
Keywords: Philosophy -- Introductions; Philosophy; Geschichte; Philosophie; Westliche Welt; Filosofie; Philosophie -- Histoire; Introductions